Social Exchange Reduces Counterproductive Work Behavior through Employee Engagement: A Moderated-Mediation Model in the Public Sector - Sanjaya, Lukman Jefri; Budiati, Yuli; Lestari, Rohmini Indah (Research Horizon, 2026)
This study investigates Counterproductive Work Behavior (CWB) among Indonesian Civil Servants, where professionalism remains suboptimal despite improvements in formal performance evaluations, indicating a gap between assessed performance and actual behavior. Grounded in social exchange theory, this research aims to examine the effects of Leader Member Exchange (LMX) and organizational justice on CWB, with work engagement as a mediating variable and emotional intelligence as a moderating variable. A quantitative research design was employed, utilizing survey data collected from 311 respondents through proportionate cluster random sampling within a regional government context. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results demonstrate that organizational justice significantly enhances work engagement and reduces CWB, while work engagement negatively affects CWB and mediates the relationship between organizational justice and CWB. Conversely, LMX and emotional intelligence do not exhibit significant direct or moderating effects. These findings suggest that fostering organizational justice and strengthening employee engagement are essential for mitigating counterproductive behaviors. In conclusion, enhancing fairness and promoting engagement constitute critical strategies for improving employee behavior in public sector organizations.